Respostas

A melhor resposta!
2013-12-13T17:17:50-02:00
F(x) = 2x + 2
f(1/2) = 2 * 1/2 + 2
f(1/2) = 2/2 + 2
f(1/2) = 1 + 2
f(1/2) = 3

f(x) = 2x + 2
f(1) = 2 * 1 + 2
f(1) = 2 + 2
f(1) = 4

f(x) = 2x + 2
f(0) = 2 * 0 + 2
f(0) = 0 + 2
f(0) =  2

f(x) = 2x + 2
f(-1) = 2 * -1 + 2
f(-1) = -2 + 2
f(-1) =  0
1 5 1
isso
mais 4x nao 40 x
50 + 4x + x(elevado a 2) = 0
F(0) = 50 + 4 * 0 + 0²
F(0) = 50 +0 + 0
F(0) = 0

Foram vendidos 50 aparelhos de faz :)
muito obrigado :D
2013-12-13T17:17:53-02:00
Só substituir o x por 1/2 ...

Y = f(x)
Y = 2.1/2 + 2
Y = 2/2 + 2
Y = 3